Clinical and Financial Outcomes With Minimally Invasive Excision With Epidermal Autografting and Poly‐Lactic Acid Skin Substitute in Adult Mid‐Deep Dermal Burns - Tony Zhao; Kaitlyn Malek; Anjay Khandelwal (International Wound Journal, 2026)
ABSTRACT Mid‐deep dermal burns have traditionally been treated with nonoperative management and split‐thickness skin grafting, but minimally invasive excision with epidermal autografting and poly‐lactic acid skin substitute (MEP) has offered an alternative approach. Comparative outcomes have remained incompletely defined. We conducted a retrospective cohort study of adult patients with mid‐deep dermal burns treated with MEP compared with a propensity score‐matched standard‐of‐care (SOC) cohort. The primary outcome was achievement of ≥ 90% wound healing by postoperative day 10, with secondary outcomes including length of stay, complications and hospital financial outcomes. Among 39 pairs analysed, MEP‐treated patients were significantly more likely to achieve early wound healing compared with SOC (82.1% vs. 45.5%, p = 0.001) and experienced fewer complications, without an increase in length of stay. Although MEP was associated with higher upfront hospital costs, reimbursement rates were comparable. MEP was associated with superior early wound healing and fewer complications without prolonging hospitalisation.